Time to active sitting position: One-year findings from a temporary COVID-19 intensive care unit. (April 2022) - Rossi, Veronica; Del Monaco, Cesare; Gambazza, Simone; Santambrogio, Martina; Binda, Filippo; Retucci, Mariangela; Privitera, Emilia; Mantero, Marco; Bottino, Nicola; Laquintana, Dario; Blasi, Francesco
Abstract: Objective: To investigate the association between time to active sitting position and clinical features in people with COVID-19 admitted to intensive care unit (ICU) and referred to physiotherapists. Method: Prospective study conducted in the largest temporary ICU in Lombardy (Italy) between April 2020 and June 2021. All individuals with COVID-19 who received physiotherapy were included. Multivariable Cox proportional hazard model was fitted to explore the statistical association between active sitting position and characteristics of patients referred to physiotherapists, also accounting for the different multidisciplinary teams responsible for patients. Results: 284 individuals over 478 (59.4%) had access to physiotherapy, which was performed for a median of 8 days, without difference between multidisciplinary teams (P = 0.446). The active sitting position was reached after a median of 18 (IQR: 10.0–32.0) days. Sex was the only characteristic associated with the time to active sitting position, with males showing a reduced hazard by a factor of 0.65 (95% CI: 0.48–0.87; P = 0.0042) compared to females. At ICU discharge, nearly 50% individuals increased Manchester Mobility Score by 3 points. During physiotherapy no major adverse event was recorded. Conclusion: Individuals with COVID-19 take long time to reach active sitting position in ICU, with males requiring longer rehabilitation than females. Highlights: Individuals with COVID-19 require long time to reach active sitting position. Sex gap in time to ASP may have clinically relevant impact on functional outcomes. A structured physiotherapy team is the key to optimize early mobilization.